1990
DOI: 10.1007/bf00016123
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of radish mitochondrial atpA: influence of nuclear background on transcription of atpA-associated sequences and relationship with male sterility

Abstract: We have previously shown that the mitochondrial gene atpA, encoding the alpha subunit of F1 ATP synthase, is associated with DNA rearrangements and nuclear-specific transcript patterns in the male-sterile cytoplasm of Ogura radish. Here we present a detailed characterization of this gene from both the normal (fertile) and Ogura (male-sterile) cytoplasms of radish to determine if it is involved in Ogura cytoplasmic male sterility. The normal and Ogura radish atpA loci are virtually identical for 3.8 kb, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…Molecular roles of Rf genes have been thought to alter mitochondrial genome structure [15,26,35], transcription and/or post-transcriptional processing of mitochondrial genes [12,13,20,22,27,38,41] that often causes modification of translation products [ 13,36]. To understand the role ofAgropyron telosomes on the restoration of normal vigor and male fertility of the alloplasmic hybrids, we compared mitochondrial genome organization and gene expression using seedlings of one representative line showing depressed vigor and the corresponding restored and control lines.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular roles of Rf genes have been thought to alter mitochondrial genome structure [15,26,35], transcription and/or post-transcriptional processing of mitochondrial genes [12,13,20,22,27,38,41] that often causes modification of translation products [ 13,36]. To understand the role ofAgropyron telosomes on the restoration of normal vigor and male fertility of the alloplasmic hybrids, we compared mitochondrial genome organization and gene expression using seedlings of one representative line showing depressed vigor and the corresponding restored and control lines.…”
Section: Introductionmentioning
confidence: 99%
“…The mitochondrial atp6 gene as a molecular marker of male sterile cytoplasm Ogura mitochondrial DNA possesses many rearrangements, including atpA, atp6 and coxI genes (Makaroff et al, 1989(Makaroff et al, , 1990(Makaroff et al, , 1991. However, the genetic roles of these rearrangements on the expression of male sterility were unclear, except atpA and coxl, which seemed to be irrelevant (Makaroff et al, 1990(Makaroff et al, , 1991.…”
Section: Discussionmentioning
confidence: 99%
“…However, the genetic roles of these rearrangements on the expression of male sterility were unclear, except atpA and coxl, which seemed to be irrelevant (Makaroff et al, 1990(Makaroff et al, , 1991. To distinguish Ogura from normal-type mtDNA, we developed a PCR assay system using atp6 as a molecular marker, and found that wild radishes with Ogura-type mtD-NA were widely distributed in Japan (Yamagishi & Terachi, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcripts by Either of Two Distinct Rf Genes Fang and McVetty (1989) nuclear influences on ogu atpA transcripts are unrelated to fertility restoration (Makaroff et al, 1990). To investigate whether the alterations in atp6 region transcripts observed in the restored plants were specifically due to the correspo^iding pol Rf genes, we analyzed the transcripts of the near isogenic lines Westar (pol) and Westar-Rf (pol) and compared these with the corresponding Westar (nap) line.…”
Section: Specific and Similar Alteration Of Pol Atp6mentioning
confidence: 99%